Emulsions of miscible solvents: the origin of anti-solvent crystallization. Issue 4 (4th January 2021) - Park, Yohwan; Song, Kwangjin; Choi, Hee Cheul
Abstract : Emulsions of miscible solvents: the origin of anti-solvent crystallization. We demonstrate that emulsions in a miscible solvents system could provide the opportunity to explain an accurate mechanism of anti-solvent crystallization before nucleation. Abstract : Emulsions are typically formed in a mixture of immiscible liquids. However, emulsion particles are also found upon mixing miscible liquids. In this paper, we suggest that emulsion particles are formed by ethanol mixed into toluene, as detected via dynamic light-scattering and small-angle X-ray scattering spectroscopy measurements. Furthermore, the addition of ethanol into a homogeneous fullerene solution (C70 /toluene) also forms emulsion particles. The emulsion particles could provide a space in which crystallization of C70 occurs via anti-solvent crystallization (ASC). The size change of the emulsion particles through coalescence and shrinkage processes, which depend on the amount of ethanol, explains the change of crystallization environment until a supersaturation state is reached. It is believed to be the previously undiscovered key indicator of the ASC mechanism prior to nucleation.